Z historii polskiego performansu. Happening, performans, intermedialność - Hendrykowski, Marek (Przestrzenie Teorii, 2019)
Marek Hendrykowski’s case study shows the original idea of The Salon Niezależnych’s performances, one of the most spectacular events of 1970s Polish student counter-culture.